ON THE HORIZON OF ADULTHOOD - BHATLAVANDE , PRAKASH; GANGAKHEDKAR (UNITED NATIONS CHILDREN'S FUND, 1999)
This book attempts to answer the common queries that exit in the minds of adolescents about human sexuality transmitted diseases including AIDS.
Keywords: HUMAN DEVELOPMENT